Răspuns :
d(A,B) = AB = V(xB-xA)² + (yB-yA)² = V(3-a)² + (a-1-2)² = V(9-6a+a²) + (a-3)² = V(a²-6a+9 + a²-6a+9) = V(2a²-12a+18)
dar AB = 2V2 => V(2a²-12a+18) = 2V2 ridici totul la a 2
2a²-12a+18 = 8
2a²-12a+10 = 0 /:2
a²-6a+5= 0, delta = 36-20= 16
a1 = (6+4)/2 = 10/2 = 5
a2 = (6-4)/2 = 2/2 = 1
deci a ={1,5}
[tex]\it AB=2\sqrt2 \Rightarrow AB^2=(2\sqrt2)^2 \Rightarrow (3-a)^2+(a-3)^2=8 \Rightarrow \\ \\ \Rightarrow (a-3)^2+(a-3)^2=8 \Rightarrow 2(a-3)^2=8|_{:2} \Rightarrow (a-3)^2=4 \Rightarrow \\ \\ \sqrt{(a-3)^2}=\sqrt4 \Rightarrow |a-3|=2 \Rightarrow a-3=\pm2 \Rightarrow a-3\in\{-2,\ 2\}|_{+3} \Rightarrow \\ \\ \Rightarrow a\in\{1,\ \ 5\}[/tex]